Feeding Difficulty Among Chinese Toddlers Aged 1–3 Years and Its Association With Health and Development - Ren, Zhongxia; Lan, Hanglian; Szeto, Ignatius Man-Yau; Yang, Chenlu; Zhang, Jian; Li, Pin; Li, Jingwen; Wang, Peiyu; Zhang, Yumei; Zhao, Ai (Frontiers in Pediatrics, 2021)
Feeding problems are biopsychosocial in nature and have a great influence on children's growth. The aim of this study was to profile the status and possible influencing factors of feeding difficulty among normal Chinese toddlers, and to investigate its association with health and development. This study is a part of the Young Investigation (YI study) conducted in 10 cities in China. Data from 924 children aged 1–3 years were analyzed. Data on socio-demographic factors, feeding behaviors, self-reported diseases, and anthropometry parameters were collected. Blood samples were drawn to determine hemoglobin levels. Feeding difficulty was evaluated by the Montreal Children's Hospital Feeding Scale (MCH-FS). Ages and Stages Questionnaires, Third Edition (ASQ-3) were used to assess developmental progress. Multivariable analyses were performed to explore the potential associations. The mean total score of the MCH-FS was 35.21 ± 12.90 and the highest scored item was “acting up/making a big fuss during mealtimes.” Feeding difficulty occurred more often among children with picky eating behavior or whose caregivers once used the strategy of pre-mastication. Children with feeding difficulty had lower intakes of cereals, vegetables, and fruits, and were more likely to suffer from diarrhea (OR, 2.04; 95%CI: 1.32, 3.11) or constipation (OR, 2.04; 95%CI: 1.27, 3.24), but not anemia. Feeding difficulty was also negatively associated with weight, height, head circumference and mid-upper-arm circumference-related Z-scores (P all < 0.05). In addition, it was related to poorer fine motor skills, personal and social skills, and total scores of ASQ-3 (β, −9.00; 95%CI: −15.11, −2.89). Feeding difficulty assessed by MCH-FS showed a negative association with children's health and development, supporting the need for early identification.